Counsellor Education As Humanist Colonialism: Seeking Postcolonial Approaches To Educating Counsellors By Exploring Pathways To An Indigenous Aesthetic Kisiku Sa’qawei Paq’tism - Bowers, R J (University Of Queensland, Aboriginal and Torres Strait Islander Studies Unit, 2008)
This narrative reflection emerged during a time of personally reconnecting with Mi’kmaq First Nation culture and heritage while working in the mainstream roles of counsellor educator and educationalist in Australia. The essay expresses turning points along a path of increasing political and social discomfort with the status quo in counsellor education. Paradoxically, and in parallel fashion, as Indigenous empowerment increased the issues that arise also became more difficult. Staying with these questions long enough to see through the fog seemed important. Disconcerting questions arose related to identity, prejudice, and healing in a field where helping is purported to be the chief focus of our work. The essay examines “Aboriginal Australian” constructs of counsellor education as expressions of liberal humanist colonialism. Pathways towards an Indigenous aesthetic are suggested based in a post-colonial model of culturally-grounded and locally-grown expressions that honour Indigenous ways of knowing. A new paradigm for counsellor education is suggested that listens to recent articulations of global Indigenous epistemology, ontology, and cosmology.